Features of the construction of directed deep wells in Turkmenistan - Deryaev, Annaguly (Italian journal of engineering geology and environment, 2024)
The relevance of the study of construction of directional deep wells in Turkmenistan lies in the application of innovative drilling methods for efficient oil production from hard-to-reach horizons, which is becoming a strategic necessity in the context of the development of the oil industry in this country. The purpose of this study was to analyse the effectiveness of the simultaneous separate operation method in the context of hydrocarbon production in one of the fields of Turkmenistan. In the course of the work the statistical method, comparative method and analysis were used. The results of the study indicated that the introduction of advanced technologies and equipment in the process of drilling and well development in the region of Turkmenistan had a profound impact on oil production. It has led not only to increased efficiency and reduced well construction time, but also increased oil production. The demand for this technology is of particular importance in western Turkmenistan, where directional drilling has become a key factor in the region’s economic development and energy security. The gamma ray logging results show fluctuations in natural radiation levels corresponding to different geological formations. Pressure curves plotted as a function of depth demonstrate fluctuations in reservoir pressure. The results of the work are of direct practical significance, allowing to accelerate the development of fields in difficult geological conditions, offshore shallow waters, as well as to reduce drilling costs without requiring changes in oil recovery factor.